2017
DOI: 10.1016/j.bjid.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for mortality in patients with ventilator-associated pneumonia caused by carbapenem-resistant Enterobacteriaceae

Abstract: The best therapeutic option for VAP by CRE is still not completely defined, but the therapy with at least two active drugs was superior in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…Observational studies comparing the outcomes for patients treated with monotherapy or combination therapy were reviewed, and control for confounders was taken into account. Most studies focused on or supplied data for BSI (212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223)(224)(225)(226)(227)(228)(229) (Table 4), while others included other types of infection (213,215,227,(230)(231)(232)(233)(234)(235)(236) (Table 5). Systematic reviews published in 2014 found major limitations in the studies analyzed and therefore could not draw strong conclusions (47,237).…”
Section: Monotherapy Versus Combination Therapymentioning
confidence: 99%
“…In particular, advanced age was shown to be an independent predictor of negative outcome in patients with K pneumoniae bloodstream infections, [ 20 ] and age>50 years was associated with increased mortality in patients with ventilator-associated pneumonia caused by CRE. [ 29 ] However, we can suppose that CAZ-AVI treatment could be effective also in older patients. Indeed, in the other case reports showing the successful treatment with CAZ-AVI, in combination with ertapenem or as monotherapy, patients were 64 or more than 70 years old, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Seven eligible studies (published in six articles) included 885 hospitalized adults with P. aeruginosa infections. Included studies were conducted between 2005 and 2012 in Brazil (5 studies [12,14,15,17,31]) and Colombia (1 study). One study was retrospective cohort and five studies were casecontrol designs ( Table 2).…”
Section: Aiat Vs Iiatmentioning
confidence: 99%
“…One study was retrospective cohort and five studies were casecontrol designs ( Table 2). The underlying site of infection was bloodstream infection (3 studies [12,15,31]), respiratory (2 studies [13,17]) and information was not reported in one study [14]. The average age of patients among included studies ranged between 50 and 73 years.…”
Section: Aiat Vs Iiatmentioning
confidence: 99%